Actas de las VII Jornadas de trabajo sobre Historia Reciente - Flier, Patricia (Coord.) (Trabajos, comunicaciones y conferencias, 2015)
Jornadas de Trabajo sobre Historia Reciente are part of a persistent concern to address from theoretical-methodological and historical-concrete perspectives the problems that this field is generating. The VII Jornadas [2014] aspire to increase and consolidate the broad development that this field of studies has had in recent years.For this, organizational forms are proposed that further promote the development of debates and exchanges, as well as other activities for the dissemination of the problems addressed in new formats that reach areas that are not strictly university.